The Vulnerable Colombian weasel Mustela felipei (Carnivora): new record from Colombia and a review of its distribution in protected areas - de Roux, Juan M.; Noguera-Urbano, Elkin A.; Ramírez-Chaves, Héctor E. (THERYA, 2019)
The Colombian weasel Mustela felipei is considered the rarest Neotropical carnivore only known from four localities in Colombia and one in Ecuador. It is considered Vulnerable on the IUCN Red List along its distributional range. We present an unexpected photographic record of a living specimen from Colombia that shed lights on its distribution on the Western Cordillera of Colombia, where it was previously known from single a record obtained on 1986. This is the first confirmed record of the Colombian weasel during the 21st century. Finally, we discuss the species’ occurrence in protected areas of Colombia, to provide tools for the conservation of this rare species.